(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This scholarly article delves deeply into the psychological experiences and inner conflicts of Santiago, the protagonist in Ernest Hemingway’s literary masterpiece “The Old Man and the Sea”. By employing a rigorous IMRAD structure, this paper dissects the existential layers of Santiago’s character, highlighting his resilience, solitude, and philosophical introspection. Through a combination of literary, psychological, and thematic analyses, the paper demonstrates how Hemingway crafts a powerful narrative of human endurance, inner strength, and spiritual triumph.